Corporate Dividend Policy And Behaviour: The Malaysian Evidence - I. M. Pandey, I. M. Pandey (Asian Academy of Management (AAM), 2003)
This study examines corporate dividend policy and behaviour of the Kuala Lumpur Stock Exchange (KLSE) companies. Our results confirm the influence of industry on payout ratios. We also find that payout ratios in a given industry vary significantly across time. The results of multinomial logit analysis reveal that the KLSE companies' dividend actions are sensitive to the changes in earnings. Probabilities of dividend increases, decreases and omissions are high, respectively, with earnings increases, decreases and losses. This causes volatility in dividend payments. The KLSE firms appear to be reluctant to omit dividend except when they suffer losses. Further, using Lintner's framework and panel data regression methodology, we find evidence in favour of regular, but less stable, dividend policies being pursued by the KLSE companies. This is contrary to the experiences of companies in the developed capital markets. The results of the two-way fixed firm and time effects model reveal that there are significant differences in dividend policies across individual firms and over time.